Amplifying Environmental Politics: Ocean Noise. Issue 5 (28th June 2017) - Ritts, Max
Abstract: Scientific evidence suggests that rising levels of anthropogenic underwater sound ("ocean noise") produced by industrial activities are causing a range of injuries to marine animals—in particular, whales. These developments have forced states and development proponents into acknowledging ocean noise as a threat to marine economic activity. This paper delivers a Gramsci‐inspired critique of the modernizations of ocean noise regulation being wrought by science, state and politics. Gramsci was acutely interested in the dynamic and social nature of scientific research, and his writings affirm science's powers and ambitions. At the same time, he was keen to observe how science participates in the process he called hegemony. Using examples drawn from Canada's West Coast, I suggest that capital is engaging ocean noise not only as a regulatory problem issuing from legal duties and legitimacy concerns, but opportunities linked to the commercialization of ocean science.